Sistem Tumpang Sari Perkebunan Karet Dalam Rangka Meningkatkan Penghasilan Penyadap Karet di Kecamatan Tanta Kabupaten Tabalong - Lara Andreiany; R Rizali (PPJP Universitas Lambung Mangkurat, 2020)
This study aimed to determine the management patterns of monoculture and intercropping rubber plants and find out which rubber plantation system was more profitable in Tanta District, Tabalong Regency. The study's scope was conducted in the Tanta Sub-district of Tabalong Regency, and the type of research was quantitative descriptive. Source of data in the form of primary data obtained from interviews conducted and processed using profit analysis techniques, revenue, production costs, and Revenue Cost Ratio (R / C).The results of the study showed that rubber plantations with intercropping patterns received higher and more profitable revenue compared to monoculture pattern rubber plantations.